Benefit of subcutaneous patient controlled analgesia after total knee arthroplasty - Yusuke Nakagawa; Toshifumi Watanabe; Yusuke Amano; Masafumi Horie; Tomomasa Nakamura; Koji Otabe; Mai Katakura; Ichiro Sekiya; Takeshi Muneta; Hideyuki Koga (Elsevier, 2019)
Purpose: Subcutaneous patient-controlled analgesia (PCA) has been widely used for orthopedic surgeries including total knee arthroplasty (TKA). This study aims to clarify the usefulness of subcutaneous PCA in the early phase after TKA. Methods: Our subjects consisted of 88 osteoarthritis knee patients who underwent primary TKA, and were classified into two groups: 42 patients received a subcutaneous PCA (containing fentanyl and droleptan) after operation (PCA group), and 46 patients were managed without a subcutaneous PCA (control group). We compared the incidence of side effects for 3 days postoperatively, measuring the number of times patients used adjuvant analgesia and range of motion on day 7 between the two groups. 34 of 42 patients in the PCA group tolerated PCA use until POD 3 (continuation sub-group), while 8 patients could not continue PCA (interruption sub-group). Demographic data of the two sub-groups were compared. Results: The mean number of times adjunctive analgesics were used by the PCA group (3.7 ± 2.2) was significantly less than in the control group (5.4 ± 2.8) (p = 0.0049). There were no significant differences in the frequency of side effects between the two groups. There was no significant difference in range of motion between the two groups. Comparing the continuation and interruption sub-groups, patients over 80 years old were at risk to discontinue a subcutaneous PCA (p = 0.0319, odds ratio 5.4). Conclusion: These findings demonstrate that subcutaneous PCA would be a safe postoperative pain regimen for TKA patients, but the effect was not enough to promote early functional recovery. Levels of evidence: Therapeutic, Level Ⅱ. Keywords: Subcutaneous patient controlled analgesia (PCA), Total knee arthroplasty (TKA). postoperative pain control